2019
DOI: 10.1111/ecog.03990
|View full text |Cite
|
Sign up to set email alerts
|

Questioning assumptions of trophic behavior in a broadly ranging marine predator guild

Abstract: We evaluated whether existing assumptions regarding the trophic ecology of a poorly‐studied predator guild, northwest (NW) Atlantic skates (family: Rajidae), were supported across broad geographic scales. Four hypotheses were tested using carbon (δ13C) and nitrogen (δ15N) stable isotope values as a proxy for foraging behavior: 1) species exhibit ontogenetic shifts in habitat and thus display a shift in 13C with differential use of the continental shelf; 2) species exhibit ontogenetic prey shifts (i.e. from sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…; Shipley et al. ); however, this cutoff has not been rigorously tested. For small fish, the probability of overlap was highest for Rainbow Smelt being found in the Cisco niche (100%) and for Bloater being found in the Kiyi niche (57%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Shipley et al. ); however, this cutoff has not been rigorously tested. For small fish, the probability of overlap was highest for Rainbow Smelt being found in the Cisco niche (100%) and for Bloater being found in the Kiyi niche (57%).…”
Section: Resultsmentioning
confidence: 99%
“…The habitat overlap probabilities ranged from near zero to 100% for small fish and up to 86% for large fish ( Figure 5). Prior studies have suggested that overlap probabilities that are >60% indicate significant niche overlap (Guzzo et al 2016;Shipley et al 2019); however, this cutoff has not been rigorously tested. For small fish, the probability of overlap was highest for Rainbow Smelt being found in the Cisco niche (100%) and for Bloater being found in the Kiyi niche (57%).…”
Section: Habitat Occupationmentioning
confidence: 99%
“…, ). A recent study utilizing carbon and nitrogen stable isotope ratios (δ 13 C and δ 15 N) suggested that Winter Skate individuals may predominantly forage within a specific latitudinal range (Shipley et al, in press), a pattern that has also been hypothesized for oceanic sharks (Bird et al. ).…”
Section: Discussionmentioning
confidence: 96%
“…Although the functional significance of these movements is difficult to ascertain without complementary approaches (e.g., ecogeochemical tracers, direct observation, or additional biotelemetry devices), complex movements may reduce resource competition with sympatric species (sensu Bizzarro et al. ), like Little Skate, which are assumed to exhibit lesser dispersal (Shipley et al., in press). This observation also underscores a limitation of passive acoustic telemetry networks that generally remain close to the shore and do not provide adequate coverage in offshore regions.…”
Section: Discussionmentioning
confidence: 99%
“…chamaeleonticeps and C . microps would (a) undergo enrichment of 15 N and 13 C with body size, indicative of ontogenetic shifts in diet and habitat use (Sánchez‐Hernández et al., 2019), (b) exhibit spatially distinct isotopic composition aligned with regional isotopic baselines (Oczkowski, Kreakie, McKinney, & Prezioso, 2016; Shipley, Olin, Power, Cerrato, & Frisk, 2019), and (c) exhibit differentiation in one or more of the measured niche axes. The coupling of isotopically derived ecological niche information with spatial and habitat characteristics offers insights into the potential drives of co‐occurrence among these understudied deep‐water species and provides a framework for future studies describing drivers of niche dynamics.…”
Section: Introductionmentioning
confidence: 99%